COUNTERACTION TO INVESTIGATION AND WAYS TO ITS OVERCOMING - Trofimovs, Igors (Administrative and Criminal Justice, 2019)
The problem of counteraction to investigation has recently gained particular topicality. . This is due to the fact that the activities of organized criminality are gaining and larger range, an essential reason of which, in its turn, are the processes of the personnel corruptibility of the power structures and law enforcement institutions.The basis of the people’s lifestyle of the adherent to the criminal environment is to put obstacles in the way of law enforcement institutions in general; and during their lifetime, because of specific mentality, criminals always and willingly put into practice various forms and methods of counteractions. As investigative practice shows, counteraction to investigation may go on during the lifetime of the counteraction performer; it may begin also in the preparation phase of a crime, or may begin or continue during investigation, trial, and even during the time of serving sentence.The purpose of this study is to clarify the essence of the counteraction concept to investigation.As a result of the study and based on the theoretical knowledge, the most important conclusion has been drawn, namely: the counteraction to investigation is an action or inaction executed on premeditated purpose to hinder or even to stop the full, objective and comprehensive clarification of the offense circumstances by the investigating authorities and courts. In the course of the study, the problems were also identified, and the means and methods of overcoming the counteraction to investigation were offered.The prevention of counteraction to investigations, identification of its motives, forecasting of counteraction forms and methods of its implementation both – at the initial period of the investigation and during the implementation of investigation activities are a part of the necessary provisions for successful neutralization of counteraction, for unmasking of counteraction performers’ activities. It is also a compulsory provision for objective, detailed and complete clarifications of all circumstances of offence, providing in this way a fair punishment for guilty persons.The application of countermeasures requires an understanding of the methods and techniques used by law enforcement authorities in investigation of criminal networks. Insufficient prevention and overcoming of counteractions to investigations is one of the reasons of qualitative and quantitative aggravation of the performance parameters of law enforcement authorities.